2018
DOI: 10.1002/chem.201804630
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Bromolactonization of Trisubstituted Olefinic Acids Catalyzed by Chiral Pyridyl Phosphoramides

Abstract: Enantioselective bromolactonization of trisubstituted olefinic acids producing synthetically useful chiral lactones with two contiguous asymmetric centers has remained mainly unexplored except for the 6-exo cyclization mode. In this work, the 5-exo- and 6-endo modes of bromocyclization of trisubstituted olefinic acids were enabled for the first time using N-bromosuccinimide and a pyridyl phosphoramide catalyst. The utility of the resulting bromolactones was demonstrated by transformations harnessing reactive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…and 88:12 e.r., for the major and minor diastereomers, respectively, Supplementary Fig. 4), comparing favorably to the only report of a small molecule catalyst for this reaction 32 . While preliminary evaluation of chlorolactonization of 1 using a subset of the enzymes ultimately screened for bromolactonization revealed no hits, subsequent analysis of 4V + S revealed that it catalyzes chlorolactonization of 1 to give 1c in 32% yield and 89:11 e.r.…”
Section: Resultssupporting
confidence: 72%
“…and 88:12 e.r., for the major and minor diastereomers, respectively, Supplementary Fig. 4), comparing favorably to the only report of a small molecule catalyst for this reaction 32 . While preliminary evaluation of chlorolactonization of 1 using a subset of the enzymes ultimately screened for bromolactonization revealed no hits, subsequent analysis of 4V + S revealed that it catalyzes chlorolactonization of 1 to give 1c in 32% yield and 89:11 e.r.…”
Section: Resultssupporting
confidence: 72%
“…and 88:12 e.r., for the major and minor diastereomers, respectively, Fig. S4), comparing favorably to the only report of a small molecule catalyst for this reaction 32 .…”
Section: Textsupporting
confidence: 75%
“…These methods are efficient and scalable, providing a modular means of assembling δ-aryl olefinic acids, which are versatile building blocks for synthesizing drugs and other biologically active compounds (Fig. 1c) 5357 .…”
Section: Introductionmentioning
confidence: 99%